Perceptional Analysis of Msmes Tax Justice Aspect - Fransiscus X N Susanto; David A A Pesudo; Michael Victor Warouw (International Journal of Social Science and Business, 2020)
This study aims to identify how the role of tax justice for taxpayer of Small and Medium sized enterprises (SMEs) will affect the level of compliance with paying taxes. The results of this study are also useful for Direktorat Jendral Pajak to identify how SMEs react to these policies so that they can represent the condition of their business in their obligation to pay taxes. This study used a qualitative method with a descriptive approach through questionnaires and in-depth interviews with respondents. The population of this study was SMEs assisted by Dinas Koperasi dan UMKM kota Salatiga with 1,656 business units with the method of determining many samples using the slovin formula measurement and with convenience sampling. The impact of the application of PP 23 of 2018 has been felt by taxpayer of SMEs since July 2018, the reduction in tax rates by half a percent of the previous tax rate has been proven to increase tax compliance for taxpayers of SMEs but the application of PP 23 of 2018 does not affect tax compliance for taxpayers of SMEs who have previously obeyed and taxpayer of SMEs with the motive to pay certain taxes.